In vitro determination of the antimicrobial potential of homemade preparations based on medicinal plants used to treat infectious diseases - GISELE MEDEIROS BASTOS; NáDIA ACCIOLY PINTO NOGUEIRA; CáSSIA LEMOS SOARES; MANUELLA RIOS MARTINS; LARISSA QUEIROZ ROCHA; ANDRéA BESSA TEXEIRA (São Paulo State University (UNESP), 2011)
The majority of the population in developing countries uses plants or plant preparations in their basic health care. Many plant species used nowadays in folk medicine have been proved to have antimicrobial properties. However, several factors, such as incorrect preparation of the plants, can interfere with the effectiveness of the treatment. The purpose of this study was to assess the use of homemade preparations of medicinal plants in the treatment of infectious diseases, by in vitro determination of their antimicrobial potential. Based on recipes elicited by questionnaires that were previously applied to a participant population, the samples were prepared in a similar manner and analyzed by the agar diffusion method. Members of 41 families, whose children attend a center of education that serves several needy communities in the city of Fortaleza (Ceará, Brazil), were interviewed; of these, 97.6% said they had used herbal therapy as a means to treat infectious diseases. In replies to a total of 39 questionnaires, 97 different homemade preparations of medicinal plants were cited. Out of 45 samples subjected to an in vitro assessment of antimicrobial activity, 25 (55.6%) had some inhibitory effect on the growth of at least one of the microorganisms used. Most of the plants with known antimicrobial properties and cited by respondents showed variations in their in vitro activity, according to the manner in which they were prepared. Keywords: Medicinal plants. Products with Antimicrobial Action. Traditional Medicine. Homemade preparation. RESUMO Determinação in vitro do potencial antimicrobiano de preparações caseiras de plantas medicinais utilizadas para o tratamento de doenças infecciosas Grande parte da população de países em desenvolvimento utiliza plantas ou preparações vegetais nos cuidados básicos à saúde. Muitas das espécies vegetais utilizadas na medicina popular apresentam propriedades antimicrobianas comprovadas; no entanto, diversos fatores, como a metodologia incorreta de preparo, podem interferir na eficácia do tratamento. O presente trabalho teve como objetivo avaliar a utilização de preparações caseiras de plantas medicinais para o tratamento de doenças infecciosas através da determinação in vitro do potencial antimicrobiano. A partir de informações contidas em questionários que foram previamente aplicados à população participante, as amostras foram preparadas de forma semelhante e analisadas através do método de difusão em ágar. Foram entrevistadas 41 famílias, das quais 97,6% afirmaram utilizar as plantas medicinais como opção terapêutica no tratamento de doenças. Em um total de 39 questionários, foram citadas 97 diferentes preparações caseiras de plantas. Das 45 amostras (indicadas para tratar algum sinal ou sintoma que podem estar relacionado a um quadro infeccioso) submetidas à avaliação da atividade antimicrobiana in vitro, 55,6% (25 amostras) apresentaram atividade inibitória sobre o crescimento de pelo menos um dos microrganismos utilizados. A maioria das plantas com propriedade antimicrobiana conhecida e que foram citadas pelos entrevistados apresentaram variações na sua atividade in vitro de acordo com o modo como foram preparadas. Palavras-chave: Plantas Medicinais. Produtos naturais com ação antimicrobiana. Medicina tradicional.